Pengembangan E-LKPD Berbasis Website Liveworksheets dengan Model Discovery Learning pada Pembelajaran IPAS di Sekolah Dasar - Putri, Mukhlisah; Raharjo, Makmum (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2024)
This research aims to develop an E-LKPD based on a liveworksheets website with a discovery learning model in elementary schools (SD). This research uses the ADDIE model development research procedure. Material expert validators and design experts validate the products. The experts' validation results categorized the E-LKPD development product as very valid. The results of this research show an excellent response from the three categories of trial groups: individual students (93%), small groups (97%), and teachers (98%). That is evidenced by the N-Gain value of 0.58, which is included in the moderate category. Thus, the E-LKPD product based on the liveworksheets website with the discovery learning model is suitable for the learning process.